Application of Exogenous Sodium Nitroprussid Alleviates Boron Toxicity in Wheat Seedlings: Investigation of Thiol Compounds, Macro/Micronutrient, and Polyamine Contents. Issue 19 (27th October 2016) - Dilek Tepe, Hafize; Aydemir, Tülin
ABSTRACT: High boron (B) levels in the soil reduce plant growth and yield production in crop plants. Nitric oxide (NO) is a highly reactive signaling molecule involved in stress response in plants. The aim of the study was to investigate the role of sodium nitroprussid (SNP), a NO donor, in alleviating the B-induced toxicity in two wheat cultivars. Both cultivars were treated with 10 mM B, 10 mM B + 0.1 mM SNP, 10 mM B + 0.2 mM SNP, and 10 mM B + 0.5 mM SNP. The nutrient contents were investigated via inductively coupled plasma mass-spectrometry. Contents of polyamines and thiol compounds were analyzed by high-performance liquid chromatography. The B toxicity caused a significant decrease in nutrient contents and thiol compounds, but increased polyamine contents. However, exogenous application of 0.2 mM SNP increased nutrient contents and thiol compounds, but lowered polyamine contents. The study clearly revealed that exogenous SNP can overcome the toxic effects of B on wheat seedlings.